2018
DOI: 10.1590/1678-4162-9787
|View full text |Cite
|
Sign up to set email alerts
|

Carcaça e componentes corporais de cordeiros lactentes em pastejo de azevém suplementados com leguminosa ou concentrado

Abstract: RESUMO O objetivo desta pesquisa foi avaliar o efeito da suplementação privativa, com concentrado ou leguminosa, sobre as características da carcaça e dos componentes corporais de cordeiros lactentes mantidos em pastejo de azevém. Foram utilizados 27 cordeiros lactentes, distribuídos nos tratamentos que corresponderam aos sistemas de alimentação: cordeiros lactentes mantidos em pasto de azevém, cordeiros lactentes mantidos em pasto de azevém e suplementados com concentrado em comedouro privativo (creep feeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Acta Scientiarum. Animal Sciences, v. 44, e53445, 2022 Regarding the systems without weaning, the neck weight was higher, the shoulder weight was similar, and the weight of other cuts obtained in the current study (Table 3) were lower than those observed by Pellegrin et al (2018) in non-weaned Texel × Ile de France lambs finished on annual ryegrass (Lolium multiflorum Lam.) pasture, supplemented or not with concentrate at 1.15% BW day -1 in creep feeding, and slaughtered at 31 kg BW.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…Acta Scientiarum. Animal Sciences, v. 44, e53445, 2022 Regarding the systems without weaning, the neck weight was higher, the shoulder weight was similar, and the weight of other cuts obtained in the current study (Table 3) were lower than those observed by Pellegrin et al (2018) in non-weaned Texel × Ile de France lambs finished on annual ryegrass (Lolium multiflorum Lam.) pasture, supplemented or not with concentrate at 1.15% BW day -1 in creep feeding, and slaughtered at 31 kg BW.…”
Section: Resultsmentioning
confidence: 54%
“…This was observed in the current study, since the LEA and the fat thickness measurements over the longissimus muscle had the highest values in the carcasses of lambs supplemented in creep feeding (Table 5). This response was not reported in other studies with purebred or crossbred lambs from late maturing breeds, such as Ile de France and Suffolk, probably due to the lower amount of concentrate supplement offered in creep feeding (around 1% BW day -1 ) (Prado et al, 2013;Pellegrin et al, 2018), or the low quality of the pasture in which this strategy was used (Ribeiro et al, 2013).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…For the variables total weight gain, daily weight gain and feed conversion, no significant differences were observed (Table 3), but the daily weight gains obtained were higher than those recommended by the NRC (2007), of 0.15 kg day -1 , demonstrating that the feed provided enough nutrients to meet the needs of the animals. High values of weight gain in sheep consuming diets containing alternative foods have been reported in research such as rice chirera diets and brewery malt powder (Carvalho et al, 2016), by-products of guava (Silva et al, 2016b), maize grain (Ferreira et al, 2016), ryegrass and legumes (Pellegrin et al, 2018), and orange pomace (Rego et al, 2019), which attribute such results to the high nutritional value of the diets used and the good acceptance by the animals.…”
Section: Resultsmentioning
confidence: 96%
“…Nevertheless, this rearing system involves the use of commercial concentrates for animal supplementation such as soybean meal, which increases production costs. In this perspective, food alternatives that do not affect animal growth, carcass yield and meat quality, and that can be incorporated into animal feed, making the activity viable, are sought (Pellegrin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%